2007
DOI: 10.1158/0008-5472.can-06-4287
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signature of Human Cancer Cell Lines Treated with the Ras Inhibitor Salirasib (S-Farnesylthiosalicylic Acid)

Abstract: Deregulation of Ras pathways results in complex abnormalities of multiple signaling cascades that contribute to human malignancies. Ras is therefore considered an appropriate target for cancer therapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 47 publications
(88 reference statements)
2
46
0
Order By: Relevance
“…Under conditions of glucose limitation, in fact, transformed cells continue to consume more glucose but are unable to upregulate mitochondrial activity. It has been shown that removal of glucose causes preferential cytotoxicity to human cancer cells compared to normal cells (Lee et al, 1998a;Spitz et al, 2000;Blum et al, 2005). This response has been connected to the production of ROS such as superoxide and hydrogen peroxide during glucose deprivation, that is, to a metabolic oxidative stress (Blackburn et al, 1999;Ahmad et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of glucose limitation, in fact, transformed cells continue to consume more glucose but are unable to upregulate mitochondrial activity. It has been shown that removal of glucose causes preferential cytotoxicity to human cancer cells compared to normal cells (Lee et al, 1998a;Spitz et al, 2000;Blum et al, 2005). This response has been connected to the production of ROS such as superoxide and hydrogen peroxide during glucose deprivation, that is, to a metabolic oxidative stress (Blackburn et al, 1999;Ahmad et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The important role of Ras in promoting glycolysis was recently demonstrated in a study, in which transformation of cells by hTERT, SV-40T/t, and H-ras caused an increase in glycolysis dependency, and as the cells progressed toward a more tumorigenic state, they became more sensitive to the glycolytic inhibitor 2-DG (Ramanathan et al, 2005). Interestingly, inhibition of H-ras by trans-farnesylthiosalicylic acid resulted in inhibition of glycolysis and cell death in human glioblastoma U87 cells, with concomitant decrease in HIF-1a and glycolytic enzymes (Blum et al, 2005).…”
Section: Hypoxiamentioning
confidence: 98%
“…These effects of FTS are manifested by a decrease in the amount of cellular Ras accompanied by interruption of the Ras-dependent Raf-1/ERK signaling cascade (45). FTS plays an antitumoral role in several non-hepatic cancer cell lines (46), and a phase I clinical trial of gemcitabine and FTS has demonstrated that FTS is well tolerated in patients with solid non-liver tumors (47). As its expression is well tolerated, salirasib may become a drug of choice for the treatment of HCC by targeting Ras and mammalian target of rapamycin (mTOR) protein kinase (48).…”
Section: Targeting Rasmentioning
confidence: 99%